Distribusi Stunting dan Determinan Stunting di Provinsi Nusa Tenggara Timur, Indonesia Tahun 2021: Analisis Spasial - Meiyetriani, Eflita; Picauly, Intje; Agung Ayu Mirah Adi, Anak; Mading, Majematang; Weraman, Pius; Boeky, Daniela L Adeline; Saleh, Asmulyati S; Peni, Jane A; Lobo, Varry; Hidayat, Ahmad Thohir; Nashriyah, Siti Fadhilatun (Jurnal Kesehatan Komunitas, 2023)
The problem of stunting is still fundamental in Indonesia's human development. East Nusa Tenggara Province is an archipelago dryland area with the highest prevalence of stunted children under five in Indonesia. This study aims to determine the relationship of child characteristics with the prevalence of stunting. This type of research is an observational study with a cross-sectional design. This study used individual secondary data from the Indonesian Nutritional Status Survey in 2021 consisting of 7,835 children under five. The results of the spatial analysis showed that in the child's characteristic factor, there was a relationship between short birth length and low birth weight with stunting prevalence. It is hoped that there will be a special model of stunting control interventions that are integrated and of high quality through multisectoral cooperation in the dryland areas of the islands of East Nusa Tenggara Province.